Teaching practices in science lessons in Icelandic compulsory schools - Pétursdóttir, Svava; Óskarsdóttir, Gunnhildur (Menntavísindasvið Háskóla Íslands, 2023)
Natural science studies involve being able to explain phenomena, apply a scientific approach and interpret data (Menntamálastofnun, 2017; Mennta- og menningarmálaráðuneyti, 2013). The European Commission (2007) has recommended inquiry-based teaching methods which emphasize student inquiry, discussions and working with student ideas. Teaching science in a real life context and integrated with other subjects is believed to encourage student interest and engagement (Kelley & Knowles, 2016) this emphasis can also be seen in the national curriculum guidelines (Mennta- og menningarmálaráðuneyti, 2013).The results of Icelandic studies show that teaching in the natural sciences could be improved (Menntamálastofnun, 2015) and that less than half of teachers have a training in teaching science (Allyson Macdonald et al., 2008; Menntamálaráðuneytið, 2005). The emphasis of the curriculum in natural science is on a variety of teaching methods such as observations, activities, links with the local environment and the use of information technology. Natural science teaching in Iceland has been studied before, showing fairly traditional teaching based on textbooks, short teacher introduction, review of homework and individual practical exercises (Birna Hugrún Bjarnadóttir et al., 2007). The aim of this study was to examine teaching methods in natural science education with an emphasis on the organization of teaching, teaching methods, the teaching environment and the tools available.The data in this study consist of observations from 23 lessons in natural sciences from the study Teaching and learning in Icelandic compulsory schools (Gerður G. Óskarsdóttir, 2014), where random lessons were observed and marked in a form including items such as classroom activities, teaching methods, layout of classrooms, tools and equipment and additional observations from 22 science lessons. Short interviews with the teachers were taken at the end of observation of lessons about how typical the lesson was with regard to assessment, access to ...